Learning Java by building Android games get ready for a fun-filled experience of learning Java by developing games for the Android platform - Horton, John (Packt Publishing, 2015)
If you are completely new to either Java, Android, or game programming and are aiming to publish Android games, then this book is for you. This book also acts as a refresher for those who already have experience in Java on another platforms or other object-oriented languages.
Includes index. - Online resource; title from cover (Safari, viewed February 19, 2015)
Keywords: Android (Electronic resource); Mobile games -- Design; Mobile games -- Development; Application software -- Development; Jeux sur mobile; Développement; Logiciels d'application; Développement; Application software; Development